Transtheoretical model on the self-care behavior of hypertension patients: a systematic review - Hasriani; Elly Lilianty Sjattar; Rosyidah Arafat (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - This review aims to describe the effectiveness of education with the transtheoretical model (TTM)-based on the self-care behavior of hypertension patients. Design/methodology/approach - A systematic literature search was carried out on four databases: PubMed, Science Direct, Cochrane and Grey literature to identify studies reported in English which were published in the last ten years. The literature search was conducted from November 13 to December 10, 2020. Findings - Based on the six studies that have been analyzed, TTM is effective in changing the stage of change and behavior of hypertension patients. These behavioral changes have an impact on the patient's controlled blood pressure. Various types of TTM-based educational interventions can be used, but the tailored behavior intervention is the most appropriate one with a minimum intervention duration of six months. Educational intervention is carried out through combine counseling and education using electronic media. Originality/value - This review presents the effectiveness of transtheoretical-based health education in changing the self-care behavior of hypertension patients accompanied by evidence-based on its implementation. There is a high and unclear risk of bias on several items influence this systematic outcome. Nevertheless, this review can still provide an overview of the effectiveness of education based on the TTM in hypertension patients about the quality results of the reviewed studies.